2012
DOI: 10.1210/jc.2011-1930
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in Serum Fibroblast Growth Factor 21 Levels in Different Subtypes of Diabetes

Abstract: Serum FGF21 level is increased in type 2 diabetes but decreased in type 1 diabetes and LADA. In autoimmune diabetes, the reduction in circulating FGF21 is closely associated with markers of pancreatic β-cell autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 20 publications
8
88
2
Order By: Relevance
“…A total of 25 adults with type 2 diabetes diagnosed within 1 year and 25 age-and sex-matched healthy control subjects were recruited at the Diabetes Center, Second Xiangya Hospital of Central South University, and the inclusion criteria were described in our previous study (22).…”
Section: Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 25 adults with type 2 diabetes diagnosed within 1 year and 25 age-and sex-matched healthy control subjects were recruited at the Diabetes Center, Second Xiangya Hospital of Central South University, and the inclusion criteria were described in our previous study (22).…”
Section: Study Cohortmentioning
confidence: 99%
“…Serum levels of C-peptide and C-reactive protein were quantified using a chemiluminescence immunoassay on a Bayer 180SE Automated Chemiluminescence System (Bayer AG, Leverkusen, Germany) and an immunoturbidimetric assay (Orion Diagnostica, Espoo, Finland), respectively. The titers of GADA, IA2A, and ZnT8A were determined by in-house radioligand assays, as previously described (22,23).…”
Section: Clinical and Biochemical Assessmentsmentioning
confidence: 99%
“…Although a previously published Chinese study [16] showed a decreased basal FGF-21 in T1DM, the basal serum FGF-21 concentration in long standing T1DM patients without residual pancreatic β-cell function has not been studied so far.…”
Section: Introductionmentioning
confidence: 95%
“…So far, only one study explored basal serum FGF-21concentration in newly diagnosed T1DM patients, describing markedly lower FGF-21 in comparison with healthy population, T2DM and latent autoimmune diabetes in adults [16]. The authors proposed that the autoimmune process destroys pancreatic β-cells and consequently reduces FGF-21 secretion in T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, blood and CSF lactate and pyruvate levels also changed following her glycemic control in our case (Table 2). Moreover, a study showed the significantly lower level of FGF21 in patients with type 1 diabetes, which was likely to show reduced insulin secretions and non-obesity, than ones with type 2 diabetes (Xiao et al 2012). Taken together with reduced insulin secretions and without obesity in our case, the substantially high FGF21 concentrations on admission might come from hyperglycemia-induced mitochondrial dysfunctions.…”
Section: Discussionmentioning
confidence: 47%